2016
DOI: 10.1177/1742395316675024
|View full text |Cite
|
Sign up to set email alerts
|

Diet modification challenges faced by marginalized and nonmarginalized adults with type 2 diabetes: A systematic review and qualitative meta-synthesis

Abstract: Objectives Diet modification is an important part of the prevention and treatment of type 2 diabetes, but sustained dietary change remains elusive for many individuals. This paper describes and interprets the barriers to diet modification from the perspective of people with type 2 diabetes, paying particular attention to the experiences of people who experience social marginalization. Methods A systematic review of primary, empirical qualitative research was performed, capturing 120 relevant studies published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 137 publications
(946 reference statements)
5
76
0
3
Order By: Relevance
“…Barriers encountered by students as discussed in week two reflect a number of generic personal and social challenges people often encounter when trying to change behaviour (Vanstone et al, 2013) and have been found when exploring perceived and real barriers to climate friendly food choices (Mäkiniemi and Vainio, 2014). Developing this insight through reflecting on personal experience and developing solutions may be important to assist students to better understand food consumption, enabling and unsupportive factors, as well as the broader determinants of sustainable food practices.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers encountered by students as discussed in week two reflect a number of generic personal and social challenges people often encounter when trying to change behaviour (Vanstone et al, 2013) and have been found when exploring perceived and real barriers to climate friendly food choices (Mäkiniemi and Vainio, 2014). Developing this insight through reflecting on personal experience and developing solutions may be important to assist students to better understand food consumption, enabling and unsupportive factors, as well as the broader determinants of sustainable food practices.…”
Section: Discussionmentioning
confidence: 99%
“…We included ethnic minorities as vulnerable populations, along with those of low socioeconomic status or living within a limited-resources setting, as these have been identified widely as fundamental causes of increased susceptibility or vulnerability to disease conditions and/or with socioeconomic obstacles to receiving appropriate and timely health care 17,18 .…”
Section: Methodsmentioning
confidence: 99%
“…However, as T2DM is a chronic condition it confronts people with new and demanding situations that require ability to tackle these challenges when needed. For example, a qualitative meta-synthesis by Vanstone et al (2017) reports that adults with T2DM have a number of different challenges when it comes to diet modification. As food has a central role in life, dietary changes affect several aspects of a person's life and generate challenges related to self-discipline, emotions, family and social support ( Vanstone et al, 2017).…”
Section: Introductionmentioning
confidence: 99%